Development of Teaching Materials in the Form of Textbooks with Contextual Nuances Equipped with Mind Map on Material of Life Organization for Junior High School Students - Defrian Melta; Rahmawati D; Ramadhan Sumarmin (ATRIUM PENDIDIKAN BIOLOGI, 2016)
The purposes of this research are to develop and identify the validity and practicality of pocket book with contextual nuance on organization of life material for Junior High School students. This research used 3 steps of 4D Models, those are define, design, and develop. The subjects of this research were 5 validators, 2 teachers, and 20 students class VII from Junior High School Number 16, Padang. Data in this research was primary data collected from validity and practicality questionnaire. The result of validity was 86,69% in valid criteria, practicality by teachers was 88,87% in practice criteria, and practicality by students was 87,48% in practice criteria.